A numerical investigation on the physical mechanisms of single track defects in selective laser melting. (November 2018) - Tang, C.; Tan, J.L.; Wong, C.H.
Highlights: A high–fidelity CFD model to simulate selective laser melting. Porosity with near–spherical shapes caused by collapse of a deep keyhole. Porosity with irregular shapes due to absence of wetting behaviour. Local thickness of next layer affected by the surface roughness of previous layer. Interlayer defects related with fluctuations of local powder thickness. Abstract: A three-dimensional high-fidelity model was developed to simulate the single track formation of stainless steel 316L during selective laser melting. Different laser powers and scanning speeds were adopted to perform the numerical simulations, revealing the underlying physics of porosity development during the melting and solidification process. Our studies suggest the importance of surface tension and recoil pressure in creating two types of porosities: near-spherical and irregular-shaped porosities. With excessive energy intensity, the predominant recoil pressure is liable to create a deep moving keyhole, resulting in entrapped gas bubbles with near-spherical geometries underneath the solidified track. Additionally, wetting behaviour between melted powders and the substrate below is proved to be significant in eliminating interlayer porosities with irregular configurations. A low energy intensity is possibly inadequate to melt the substrate below, suppressing the wetting behaviour and giving rise to the formation of interlayer defects. Furthermore, our multilayer simulations prove that the surface roughness of previously solidified layer plays a critical role in affecting the local thickness of next powder layer. The fluctuation of local powder thickness is probably associated with the formation of interlayer defects, as the energy intensity maybe not strong enough to penetrate a locally thicker powder layer.